DIPLOMASI AKADEMIK BERBASIS DATA: KEMITRAAN BADAN PENJAMINAN MUTU UNESA DAN NAKHON PHANOM UNIVERSITY DALAM INTERNASIONALISASI SISTEM PENJAMINAN MUTU INTERNAL - Widowati Budijastuti; Bertha Yonata (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
The internationalization of quality assurance systems is now a strategic agenda for Indonesian higher education institutions, particularly since Ministerial Regulation (Permendiktisaintek) No. 39 of 2025 pushed universities to move beyond national standards and toward global ones. Rather than reading as a standard training-evaluation report, this article frames the partnership between the Quality Assurance Agency (BPM) of Universitas Negeri Surabaya (Unesa) and Nakhon Phanom University (NPU), Thailand, as a form of academic diplomacy aimed at strengthening cross-border Internal Quality Assurance Systems (SPMI). The partnership unfolded in three stages, two online sessions followed by one in-person session, transferring Unesa's nationally proven practices in quality audit, monitoring, and Importance-Performance Analysis (IPA)-based survey analysis. The impact evaluation points to strong acceptance of both the program's substance and its facilitation: the average performance score (3.19) exceeded the average importance score (2.79), most indicators fell in the Maintain quadrant, and none landed in the Overinvest quadrant. These findings suggest that a staged online-offline collaboration model is an efficient, sustainable way to disseminate an international quality culture, and one worth replicating at other universities preparing for SPMI internationalization.